Valency Dictionaries and Chinese Vocabulary Acquisition for Foreign Learners - Gao, Jun; Liu, Haitao (Lexikos, 2020)
Valency is a major source of lexical errors in foreign language learning. Accordingly, the research question is how the syntactic and semantic properties of a word can be retrieved from the corpora and represented in a Chinese valency dictionary to facilitate foreign learners’ vocabulary acquisition. Within the three aspects of the valency framework — logical-semantic, syntactic and semantic-pragmatic valency — this study examines 60 cases of Chinese lexical misuse extracted from the HSK (Chinese Language Proficiency Test) Dynamic Compositions Corpus. The results suggest that the majority of cases of misuse occur in the dimension of semantic-pragmatic valency and that this semantic-pragmatic misuse can be ascribed to various factors such as semantic collocations, emotive variables, text styles, registers, and other contextual factors. The results are then utilized as syntactic, semantic and pragmatic information to be presented in a Chinese valency dictionary. Specifically, the results obtained from a case study of a misused word by referring to a large-scale native Chinese speaker corpus help retrieve a relatively full list of complementation patterns, based on which the study designs a Chinese valency entry that embodies three basic elements — quantitative valency, qualitative valency and valency patterns.